Preparation process of polyurethane nanoscale microporous membrane for protective clothing

The mixture of modified silk fibroin and polyurethane material and the addition of modified cellulose and aerogel powder to breathable particles are solved, and the deficiencies of the polyurethane microporous membrane in terms of fracture strength, modulus and breathability are achieved, and higher mechanical properties and breathable effects are achieved.

CN119613802AActive Publication Date: 2025-03-14ZHANGJIAGANG HONGYU ARTIFICIAL LEATHER

Patent Information

Application Number
CN202510168256.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-03-14
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The existing polyurethane microporous membranes are insufficient in terms of fracture strength and modulus, have limited improvement in breathability, and are not effective in use in humid environments.

Method used

Modified silk fibroin is used to mix with polyurethane material, and breathable particles obtained by mixing modified cellulose and aerogel powder are added. The overall performance of the material and the stability of the preparation process are improved by acetylation treatment and dopamine hydrochloride.

Benefits of technology

It significantly improves the fracture strength and modulus of the film, optimizes the breathable performance, enhances the use effect in humid environments, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a preparation technology of a polyurethane nanoscale microporous membrane for protective clothing, and belongs to the technical field of clothing fabric preparation, and the preparation technology specifically comprises the following steps: extracting silk fibroin and carrying out hydrophobic modification to obtain modified silk fibroin; then, the modified cellulose and polyurethane are mixed and dissolved in a solvent, a pore-forming agent and breathable particles obtained by mixing the modified cellulose and aerogel powder are added, and a mother solution is prepared; and finally, preparing a membrane by using the mother liquor, thereby obtaining the polyurethane nano-scale microporous membrane for the protective clothing. According to the process, modified silk fibroin and a polyurethane material are mixed, and breathable particles obtained by mixing modified cellulose and aerogel powder are added, so that the mechanical property of the membrane is remarkably improved, and the breathability is optimized. Meanwhile, through acetylation treatment on silk fibroin and modification on carboxymethyl cellulose by using dopamine hydrochloride, the overall performance of the material and the stability in the preparation process are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of clothing fabric preparation, and more specifically, to a preparation process of a polyurethane nano-scale microporous membrane for protective clothing. Background Art

[0002] In the field of modern protective clothing materials, polyurethane microporous membranes are widely used due to their unique air permeability and certain waterproof properties. However, the polyurethane microporous membranes prepared by the prior art still have some shortcomings.

[0003] First, traditional polyurethane microporous membranes often fail to reach ideal levels in terms of breaking strength and modulus, limiting their application in high-strength applications. This is mainly because the materials used in traditional preparation processes cannot fully utilize their respective advantages, resulting in limited improvement in the overall performance of the membrane. For example, although some natural polymer materials have high strength and toughness, they have poor compatibility with polyurethane materials and are difficult to form a stable structure after mixing.

[0004] Secondly, the existing technology still has bottlenecks in improving the air permeability of the membrane. Although the traditional method of adding breathable particles can increase the number of micropores in the membrane to a certain extent, the distribution and uniformity of the micropores are often difficult to control, resulting in insufficient improvement in air permeability. In addition, the addition of breathable particles may also affect the hydrophobic properties of the membrane, greatly reducing the effectiveness of protective clothing in humid environments.

[0005] Based on the above statements, the present application provides a process for preparing a polyurethane nano-scale microporous membrane for protective clothing. Summary of the invention

[0006] In order to solve the problems raised by the background technology, the present application provides a process for preparing a polyurethane nano-scale microporous membrane for protective clothing. The present invention proposes a brand-new process for preparing a polyurethane nano-scale microporous membrane. The process significantly improves the breaking strength and modulus of the membrane and optimizes the air permeability by mixing modified silk fibroin with polyurethane materials and adding breathable particles obtained by mixing modified cellulose and aerogel powder. At the same time, the overall performance of the material and the stability during the preparation process are further improved by acetylation of silk fibroin and modification of carboxymethyl cellulose with dopamine hydrochloride. These innovations make the present invention have significant advantages and application prospects in the field of preparation of polyurethane microporous membranes for protective clothing.

[0007] The present application provides a preparation process of a polyurethane nano-scale microporous membrane for protective clothing, which adopts the following technical solution: A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, comprising the following preparation steps: S1, extracting silk fibroin, and hydrophobically modifying the silk fibroin to prepare modified silk fibroin; S2, mixing the modified silk fibroin obtained in step S1 with polyurethane in a solvent, stirring at room temperature until dissolved, adding a pore-forming agent and breathable particles to obtain a mother solution; S3, using the mother solution obtained in step S2 to prepare a membrane, thereby obtaining a polyurethane nano-scale microporous membrane for protective clothing; The breathable particles are obtained by mixing modified cellulose and aerogel powder.

[0008] Furthermore, in step S1, the modified silk fibroin is prepared by the following steps: S11, mixing urea and guanidine hydrochloride, and heating to obtain a protein sol solution; then chopping the silk fibers, adding them to the protein sol solution, stirring evenly, raising the system temperature for 20-30 hours, washing, filtering, and obtaining silk fibroin; S12. Add silk fibroin to deionized water, increase the system temperature to 50-60°C, stir, then add acetic anhydride and adjust the pH value of the system to 9-10, continue the reaction for 1-3 hours, then adjust the pH value of the system to neutral, dialyze at 0-4°C to obtain modified silk fibroin.

[0009] Furthermore, in step S1, the modified silk fibroin is prepared by the following steps: S11, urea and guanidine hydrochloride are mixed in a mass ratio of 2:1, and then the system temperature is increased to 90°C, and heated for 2 hours to obtain a protein sol solution; then the silk fiber is chopped and added to the protein sol solution in a mass ratio of 1:100, and the system temperature is increased to 100°C after stirring evenly, and after treating for 24 hours, the silk fiber is washed with deionized water and filtered to obtain silk fibroin; S12. Add silk fibroin into deionized water at a mass volume ratio of 1 g: 5-10 mL, increase the system temperature to 50-60°C, stir at 30-90 rpm for 10-15 minutes, then add acetic anhydride and use NaOH solution to adjust the system pH to 9-10, continue the reaction for 1-3 hours, then use HCl solution to adjust the system pH to neutral, dialyze at 0-4°C for 48 hours to obtain modified silk fibroin.

[0010] Furthermore, in the above reaction process, protein glue solution is used to extract silk fibroin from silk fibers, and then acetic anhydride is used as an acylating agent to modify the silk fibroin. The acylating agent is used to undergo a nucleophilic substitution reaction with the amino group in the protein molecule to introduce a hydrophobic acetyl group into the protein, and the protein structure is changed to expose more hydrophobic groups, thereby preparing modified silk fibroin.

[0011] Furthermore, in step S12, the amount of silk fibroin and acetic anhydride used is 1:(0.2-0.3).

[0012] Furthermore, in step S2, the mass ratio of modified silk fibroin, polyurethane, pore-forming agent and breathable particles is (20-30):100:(5-10):(10-20).

[0013] Furthermore, the pore-forming agent is nano zinc oxide.

[0014] Furthermore, in step S3, the air permeable particles are prepared by the following steps: S21, adding 2-morpholineethanesulfonic acid to deionized water, adjusting the pH value of the system to 5.5-6.7, and stirring the system at room temperature until dissolved to obtain 2-morpholineethanesulfonic acid buffer; dissolving carboxymethyl cellulose, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and dopamine hydrochloride in the 2-morpholineethanesulfonic acid buffer, and stirring at room temperature under an inert gas atmosphere to obtain modified cellulose; S22. Add sodium alginate into deionized water, stir evenly at room temperature, add calcium chloride solution into the system, stir for 10-30 minutes, freeze-dry, then crush and sieve to obtain aerogel powder; mix the aerogel powder with the modified cellulose obtained in step S21 to obtain breathable particles.

[0015] Furthermore, in step S3, the air permeable particles are prepared by the following steps: S21, 0.5-0.8 g of 2-morpholineethanesulfonic acid is added to 30 mL of deionized water, a NaOH solution is used to adjust the pH value of the system to 5.5-6.7, and the system is stirred at room temperature until dissolved to obtain a 2-morpholineethanesulfonic acid buffer; carboxymethyl cellulose, 0.192 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.115 g of N-hydroxysuccinimide and dopamine hydrochloride are dissolved in 10 mL of 2-morpholineethanesulfonic acid buffer, and stirred at room temperature under an inert gas atmosphere for 24 hours to obtain modified cellulose; S22. Add sodium alginate into deionized water at a mass volume ratio of (1-3) g:100 mL, stir evenly at room temperature, add 10-20 mL of 3.5 wt% calcium chloride solution into the system, stir at 60-120 rpm for 10-30 minutes, freeze-dry the system at -40°C for 2-3 hours, then crush and pass through a 100 mesh sieve to obtain aerogel powder; mix the aerogel powder with the modified cellulose obtained in step S21 to obtain breathable particles.

[0016] Furthermore, in the above reaction process, carboxymethyl cellulose is modified by using dopamine hydrochloride, and the amino groups on dopamine hydrochloride and the carboxyl groups on carboxymethyl cellulose undergo amidation reaction in the EDC / NHS system, thereby introducing amide groups and catechol groups on the carboxymethyl cellulose to prepare modified cellulose. The modified cellulose is mixed with sodium alginate aerogel powder to obtain breathable particles.

[0017] Furthermore, in step S21, the mass ratio of carboxymethyl cellulose to dopamine hydrochloride is (5-10):(0.1-1).

[0018] Furthermore, the mass ratio of aerogel powder to modified cellulose is 1:(0.2-0.4).

[0019] Furthermore, the specific operation of using the mother solution obtained in step S2 to prepare the membrane is as follows: The mother solution was ultrasonically mixed for 10-20 minutes, then coated on a stainless steel substrate, naturally cured for 10-30 minutes, then washed with deionized water, and vacuum dried.

[0020] Furthermore, the polyurethane is a polyurethane material containing a benzene ring structure.

[0021] In summary, this application has the following beneficial effects: 1. In the technical solution of the present invention, modified silk fibroin is mixed with polyurethane material for the preparation of microporous membrane, and breathable particles obtained by mixing modified cellulose and aerogel powder are added. As a natural polymer material, silk fibroin has high strength and toughness. After mixing with polyurethane material, it can give play to its respective advantages and significantly improve the breaking strength and modulus of the membrane. The addition of breathable particles, especially the combination of modified cellulose and aerogel powder, can form more micropores in the membrane. These micropores help to improve the air permeability of the membrane, allowing air or gas to pass through the membrane layer more easily, achieving a hydrophobic and breathable effect.

[0022] 2. In the technical solution of the present invention, the silk fibroin is acetylated, a hydrophobic acetyl group is introduced into the silk fibroin, and the acylation degree of the silk fibroin is increased by increasing the usage amount of the acylating agent, exposing more hydrophobic groups on the protein, further improving the hydrophobicity of the protein and the dissolution effect in the solvent. The polyurethane material itself has a microphase separation structure, and the hard segment and the soft segment thereon have a tendency to separate spontaneously in thermodynamics. The silk fibroin after acylation modification has a more stretched structure, which has the effect of promoting the interaction and dispersion between the hard segment and the soft segment of the polyurethane, thereby further stabilizing the microphase separation structure and improving the overall performance of the material.

[0023] 3. In the technical solution of the present invention, carboxymethyl cellulose is modified with dopamine hydrochloride and then mixed with sodium alginate aerogel powder to prepare breathable particles. The modified carboxymethyl cellulose can have good dispersion stability in the polyurethane matrix through π-π interaction, and can form covalent bonds with amino groups on silk fibroin through Michael addition, and form metal ion coordination bonds with pore-forming agent nano zinc oxide, further promoting uniform dispersion of various components in the system, preventing pore-forming agent agglomeration, and improving the uniformity of pores in porous membrane products. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The specific implementation methods of this application involve: Carboxymethyl cellulose: brand is Sigma-Aldrich, product number is 1096611.

[0026] Polyurethane: diphenylmethane diisocyanate (MDI) type polyurethane.

[0027] Nano zinc oxide: provided by Shandong Xingya New Materials Co., Ltd., with an average particle size of 30-50nm and a particle size less than 100nm.

[0028] Example 1

[0029] The present application provides a preparation process of a polyurethane nano-scale microporous membrane for protective clothing, which adopts the following technical solution: A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, specifically comprising the following preparation steps: S1, extracting silk fibroin, performing hydrophobic modification on the silk fibroin, and preparing modified silk fibroin, the specific operation is as follows: S11, urea and guanidine hydrochloride are mixed in a mass ratio of 2:1, and then the system temperature is increased to 90°C, and heated for 2 hours to obtain a protein sol solution; then the silk fiber is chopped and added to the protein sol solution in a mass ratio of 1:100, and the system temperature is increased to 100°C after stirring evenly, and after treating for 24 hours, the silk fiber is washed with deionized water and filtered to obtain silk fibroin; S12. Add silk fibroin into deionized water at a mass volume ratio of 1 g:5 mL, raise the system temperature to 50°C, stir at 30 rpm for 10 minutes, then add acetic anhydride and use NaOH solution to adjust the system pH to 9, continue the reaction for 1 hour, then use HCl solution to adjust the system pH to neutral, dialyze at 0°C for 48 hours to obtain modified silk fibroin; wherein, the amount of silk fibroin to acetic anhydride used is 1:0.2.

[0030] S2, mixing the modified silk fibroin obtained in step S1 with polyurethane in a tetrahydrofuran solvent at a mass volume ratio of 1 g:5 mL, stirring at room temperature until dissolved, adding a pore-forming agent and breathable particles to obtain a mother solution; wherein the mass ratio of the modified silk fibroin, polyurethane, pore-forming agent and breathable particles is 20:100:5:10; The pore-forming agent used is nano zinc oxide; The air-permeable particles are prepared by the following steps: S21, 0.5g of 2-morpholineethanesulfonic acid was added to 30mL of deionized water, and the pH value of the system was adjusted to 5.5 with a NaOH solution, and the system was stirred at room temperature until dissolved to obtain a 2-morpholineethanesulfonic acid buffer; 5g of carboxymethyl cellulose, 0.192g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.115g of N-hydroxysuccinimide and 0.1g of dopamine hydrochloride were dissolved in 10mL of 2-morpholineethanesulfonic acid buffer, and stirred at room temperature under a nitrogen atmosphere for 24 hours to obtain modified cellulose; S22. Add sodium alginate to deionized water at a mass volume ratio of 1 g: 100 mL, stir evenly at room temperature, add 10 mL of 3.5 wt% calcium chloride solution to the system, stir at 60 rpm for 10 minutes, freeze-dry the system at -40 ° C for 2 hours, then crush and pass through a 100 mesh sieve to obtain aerogel powder; mix the aerogel powder with the modified cellulose obtained in step S21 to obtain breathable particles; wherein the mass ratio of aerogel powder to modified cellulose is 1:0.2.

[0031] S3. Use the mother liquor obtained in step S2 to prepare a membrane. Ultrasonic mix the mother liquor for 10 minutes, then coat it on a stainless steel substrate, naturally cure it for 10 minutes, then wash it with deionized water for 3 times, and vacuum dry it under 1Pa and -55°C to obtain a polyurethane nano-scale microporous membrane for protective clothing.

[0032] Example 2

[0033] A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, specifically comprising the following preparation steps: S1, extracting silk fibroin, performing hydrophobic modification on the silk fibroin, and preparing modified silk fibroin, the specific operation is as follows: S11, urea and guanidine hydrochloride are mixed in a mass ratio of 2:1, and then the system temperature is increased to 90°C, and heated for 2 hours to obtain a protein sol solution; then the silk fiber is chopped and added to the protein sol solution in a mass ratio of 1:100, and the system temperature is increased to 100°C after stirring evenly, and after treating for 24 hours, the silk fiber is washed with deionized water and filtered to obtain silk fibroin; S12. Add silk fibroin into deionized water at a mass volume ratio of 1 g:8 mL, raise the system temperature to 55°C, stir at 60 rpm for 10 minutes, then add acetic anhydride and use NaOH solution to adjust the system pH to 9, continue the reaction for 2 hours, then use HCl solution to adjust the system pH to neutral, dialyze at 0°C for 48 hours to obtain modified silk fibroin; wherein, the amount of silk fibroin to acetic anhydride used is 1:0.25.

[0034] S2, mixing the modified silk fibroin obtained in step S1 with polyurethane in a tetrahydrofuran solvent at a mass volume ratio of 1 g:5 mL, stirring at room temperature until dissolved, adding a pore-forming agent and breathable particles to obtain a mother solution; wherein the mass ratio of the modified silk fibroin, polyurethane, pore-forming agent and breathable particles is 25:100:7:15; The pore-forming agent used is nano zinc oxide; The air-permeable particles are prepared by the following steps: S21, 0.65g of 2-morpholineethanesulfonic acid was added to 30mL of deionized water, and the pH value of the system was adjusted to 6.1 with a NaOH solution, and the system was stirred at room temperature until dissolved to obtain a 2-morpholineethanesulfonic acid buffer; 8g of carboxymethyl cellulose, 0.192g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.115g of N-hydroxysuccinimide and 0.5g of dopamine hydrochloride were dissolved in 10mL of 2-morpholineethanesulfonic acid buffer, and stirred at room temperature under a nitrogen atmosphere for 24 hours to obtain modified cellulose; S22. Add sodium alginate to deionized water at a mass volume ratio of 2g:100mL, stir evenly at room temperature, add 15mL of 3.5wt% calcium chloride solution to the system, stir at 90rpm for 20 minutes, freeze-dry the system at -40°C for 2.5 hours, then crush and pass through a 100-mesh sieve to obtain aerogel powder; mix the aerogel powder with the modified cellulose obtained in step S21 to obtain breathable particles; wherein the mass ratio of the aerogel powder to the modified cellulose is 1:0.3.

[0035] S3. Use the mother liquor obtained in step S2 to prepare a membrane. Ultrasonic mix the mother liquor for 15 minutes, then coat it on a stainless steel substrate, naturally cure it for 20 minutes, then wash it with deionized water for 3 times, and vacuum dry it under 1Pa and -55°C to obtain a polyurethane nano-scale microporous membrane for protective clothing.

[0036] Example 3

[0037] A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, specifically comprising the following preparation steps: S1, extracting silk fibroin, performing hydrophobic modification on the silk fibroin, and preparing modified silk fibroin, the specific operation is as follows: S11, urea and guanidine hydrochloride are mixed in a mass ratio of 2:1, and then the system temperature is increased to 90°C, and heated for 2 hours to obtain a protein sol solution; then the silk fiber is chopped and added to the protein sol solution in a mass ratio of 1:100, and the system temperature is increased to 100°C after stirring evenly, and after treating for 24 hours, the silk fiber is washed with deionized water and filtered to obtain silk fibroin; S12. Add silk fibroin into deionized water at a mass volume ratio of 1 g:10 mL, raise the system temperature to 60°C, stir at 90 rpm for 15 minutes, then add acetic anhydride and use NaOH solution to adjust the system pH to 10, continue the reaction for 3 hours, then use HCl solution to adjust the system pH to neutral, dialyze at 4°C for 48 hours to obtain modified silk fibroin; wherein, the amount of silk fibroin to acetic anhydride used is 1:0.3.

[0038] S2, mixing the modified silk fibroin obtained in step S1 with polyurethane in a tetrahydrofuran solvent at a mass volume ratio of 1 g:5 mL, stirring at room temperature until dissolved, adding a pore-forming agent and breathable particles to obtain a mother solution; wherein the mass ratio of the modified silk fibroin, polyurethane, pore-forming agent and breathable particles is 30:100:10:20; The pore-forming agent used is nano zinc oxide; The air permeable particles are prepared by the following steps: S21, 0.8 g of 2-morpholineethanesulfonic acid was added to 30 mL of deionized water, and the pH value of the system was adjusted to 6.7 with a NaOH solution, and the system was stirred at room temperature until dissolved to obtain a 2-morpholineethanesulfonic acid buffer; 10 g of carboxymethyl cellulose, 0.192 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.115 g of N-hydroxysuccinimide and 1.0 g of dopamine hydrochloride were dissolved in 10 mL of 2-morpholineethanesulfonic acid buffer, and stirred at room temperature under a nitrogen atmosphere for 24 hours to obtain modified cellulose; S22. Add sodium alginate to deionized water at a mass volume ratio of 3g:100mL, stir evenly at room temperature, add 20mL of 3.5wt% calcium chloride solution to the system, stir at 120rpm for 10-30 minutes, freeze-dry the system at -40°C for 3 hours, then crush and pass through a 100-mesh sieve to obtain aerogel powder; mix the aerogel powder with the modified cellulose obtained in step S21 to obtain breathable particles; wherein the mass ratio of the aerogel powder to the modified cellulose is 1:0.4.

[0039] S3. Use the mother liquor obtained in step S2 to prepare a membrane. Ultrasonic mix the mother liquor for 20 minutes, then coat it on a stainless steel substrate, naturally cure it for 30 minutes, then wash it with deionized water for 3 times, and vacuum dry it under 1Pa and -55°C to obtain a polyurethane nano-scale microporous membrane for protective clothing.

[0040] Comparative Example 1 The difference between this comparative example and Example 1 is that the silk fibroin is not modified in this comparative example, and the specific operation is as follows: A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, specifically comprising the following preparation steps: S1. Extracting silk fibroin, the specific operation is as follows: Urea and guanidine hydrochloride were mixed at a mass ratio of 2:1, and then the system temperature was raised to 90°C. After heating for 2 hours, a protein sol solution was obtained. Then, the silk fibers were chopped and added to the protein sol solution at a mass ratio of 1:100. After stirring evenly, the system temperature was raised to 100°C. After treatment for 24 hours, the fibers were washed with deionized water and filtered to obtain silk fibroin. S2, mixing the silk fibroin obtained in step S1 with the polyurethane in a tetrahydrofuran solvent at a mass volume ratio of 1 g:5 mL, stirring at room temperature until dissolved, adding a pore-forming agent and breathable particles to obtain a mother solution; wherein the mass ratio of the silk fibroin, the polyurethane, the pore-forming agent and the breathable particles is 20:100:5:10; The pore-forming agent used is nano zinc oxide; The air-permeable particles are prepared by the following steps: S21, 0.5g of 2-morpholineethanesulfonic acid was added to 30mL of deionized water, and the pH value of the system was adjusted to 5.5 with a NaOH solution, and the system was stirred at room temperature until dissolved to obtain a 2-morpholineethanesulfonic acid buffer; 5g of carboxymethyl cellulose, 0.192g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.115g of N-hydroxysuccinimide and 0.1g of dopamine hydrochloride were dissolved in 10mL of 2-morpholineethanesulfonic acid buffer, and stirred at room temperature under a nitrogen atmosphere for 24 hours to obtain modified cellulose; S22. Add sodium alginate to deionized water at a mass volume ratio of 1 g: 100 mL, stir evenly at room temperature, add 10 mL of 3.5 wt% calcium chloride solution to the system, stir at 60 rpm for 10 minutes, freeze-dry the system at -40 ° C for 2 hours, then crush and pass through a 100 mesh sieve to obtain aerogel powder; mix the aerogel powder with the modified cellulose obtained in step S21 to obtain breathable particles; wherein the mass ratio of aerogel powder to modified cellulose is 1:0.2.

[0041] S3. Use the mother liquor obtained in step S2 to prepare a membrane. Ultrasonic mix the mother liquor for 10 minutes, then coat it on a stainless steel substrate, naturally cure it for 10 minutes, then wash it with deionized water for 3 times, and vacuum dry it under 1Pa and -55°C to obtain a polyurethane nano-scale microporous membrane for protective clothing.

[0042] Comparative Example 2 The difference between this comparative example and Example 1 is that the air-permeable particles in this comparative example are obtained by mixing carboxymethyl cellulose and aerogel powder, and the specific operation is as follows: A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, specifically comprising the following preparation steps: S1, extracting silk fibroin, performing hydrophobic modification on the silk fibroin, and preparing modified silk fibroin, the specific operation is as follows: S11, urea and guanidine hydrochloride are mixed in a mass ratio of 2:1, and then the system temperature is increased to 90°C, and heated for 2 hours to obtain a protein sol solution; then the silk fiber is chopped and added to the protein sol solution in a mass ratio of 1:100, and the system temperature is increased to 100°C after stirring evenly, and after treating for 24 hours, the silk fiber is washed with deionized water and filtered to obtain silk fibroin; S12. Add silk fibroin into deionized water at a mass volume ratio of 1 g:5 mL, raise the system temperature to 50°C, stir at 30 rpm for 10 minutes, then add acetic anhydride and use NaOH solution to adjust the system pH to 9, continue the reaction for 1 hour, then use HCl solution to adjust the system pH to neutral, dialyze at 0°C for 48 hours to obtain modified silk fibroin; wherein, the amount of silk fibroin to acetic anhydride used is 1:0.2.

[0043] S2, mixing the modified silk fibroin obtained in step S1 with polyurethane in a tetrahydrofuran solvent at a mass volume ratio of 1 g:5 mL, stirring at room temperature until dissolved, adding a pore-forming agent and breathable particles to obtain a mother solution; wherein the mass ratio of the modified silk fibroin, polyurethane, pore-forming agent and breathable particles is 20:100:5:10; The pore-forming agent used is nano zinc oxide; The air permeable particles are prepared by the following steps: S21. Add sodium alginate into deionized water at a mass volume ratio of 1 g: 100 mL, stir evenly at room temperature, add 10 mL of 3.5 wt% calcium chloride solution to the system, stir at 60 rpm for 10 minutes, freeze-dry the system at -40°C for 2 hours, then crush and sieve through a 100-mesh sieve to obtain aerogel powder; mix the aerogel powder with carboxymethyl cellulose to obtain breathable particles; wherein the mass ratio of aerogel powder to carboxymethyl cellulose is 1:0.2.

[0044] S3. Use the mother liquor obtained in step S2 to prepare a membrane. Ultrasonic mix the mother liquor for 10 minutes, then coat it on a stainless steel substrate, naturally cure it for 10 minutes, then wash it with deionized water for 3 times, and vacuum dry it under 1Pa and -55°C to obtain a polyurethane nano-scale microporous membrane for protective clothing.

[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that the air-permeable particles in this comparative example are aerogel powders, and the specific operation is as follows: A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, specifically comprising the following preparation steps: S1, extracting silk fibroin, performing hydrophobic modification on the silk fibroin, and preparing modified silk fibroin, the specific operation is as follows: S11, urea and guanidine hydrochloride are mixed in a mass ratio of 2:1, and then the system temperature is increased to 90°C, and heated for 2 hours to obtain a protein sol solution; then the silk fiber is chopped and added to the protein sol solution in a mass ratio of 1:100, and the system temperature is increased to 100°C after stirring evenly, and after treating for 24 hours, the silk fiber is washed with deionized water and filtered to obtain silk fibroin; S12. Add silk fibroin into deionized water at a mass volume ratio of 1 g:5 mL, raise the system temperature to 50°C, stir at 30 rpm for 10 minutes, then add acetic anhydride and use NaOH solution to adjust the system pH to 9, continue the reaction for 1 hour, then use HCl solution to adjust the system pH to neutral, dialyze at 0°C for 48 hours to obtain modified silk fibroin; wherein, the amount of silk fibroin to acetic anhydride used is 1:0.2.

[0046] S2, mixing the modified silk fibroin obtained in step S1 with polyurethane in a tetrahydrofuran solvent at a mass volume ratio of 1 g:5 mL, stirring at room temperature until dissolved, adding a pore-forming agent and breathable particles to obtain a mother solution; wherein the mass ratio of the modified silk fibroin, polyurethane, pore-forming agent and breathable particles is 20:100:5:10; The pore-forming agent used is nano zinc oxide; The air permeable particles are prepared by the following steps: Sodium alginate was added into deionized water at a mass volume ratio of 1 g:100 mL, and stirred evenly at room temperature. 10 mL of 3.5 wt% calcium chloride solution was added into the system, and stirred at 60 rpm for 10 minutes. The system was freeze-dried at -40 °C for 2 hours, and then crushed and passed through a 100-mesh sieve to obtain breathable particles.

[0047] S3. Use the mother liquor obtained in step S2 to prepare a membrane. Ultrasonic mix the mother liquor for 10 minutes, then coat it on a stainless steel substrate, naturally cure it for 10 minutes, then wash it with deionized water for 3 times, and vacuum dry it under 1Pa and -55°C to obtain a polyurethane nano-scale microporous membrane for protective clothing.

[0048] Comparative Example 4 The difference between this comparative example and Example 1 is that a small amount of acetic anhydride is used to modify the silk fibroin in this comparative example. The specific operation is as follows: A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, specifically comprising the following preparation steps: S1, extracting silk fibroin, performing hydrophobic modification on the silk fibroin, and preparing modified silk fibroin. The specific difference is that in step S12, the amount of silk fibroin and acetic anhydride used is 1:0.1.

[0049] Comparative Example 5 The difference between this comparative example and Example 1 is that in this comparative example, silk fibroin is not used to enhance the microporous membrane product. The specific operation is as follows: A preparation process of a polyurethane nano-scale microporous membrane for protective clothing, specifically comprising the following preparation steps: S1. Mix the polyurethane in tetrahydrofuran solvent at a mass volume ratio of 1 g:5 mL, stir until dissolved at room temperature, add a pore-forming agent and breathable particles to obtain a mother solution; wherein the mass ratio of the polyurethane, the pore-forming agent and the breathable particles is 120:5:10; The pore-forming agent used is nano zinc oxide; The air-permeable particles are prepared by the following steps: 1. Add 0.5 g of 2-morpholineethanesulfonic acid to 30 mL of deionized water, adjust the pH value of the system to 5.5 with a NaOH solution, and stir the system at room temperature until dissolved to obtain a 2-morpholineethanesulfonic acid buffer solution; dissolve 5 g of carboxymethyl cellulose, 0.192 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.115 g of N-hydroxysuccinimide and 0.1 g of dopamine hydrochloride in 10 mL of 2-morpholineethanesulfonic acid buffer solution, and stir at room temperature and under a nitrogen atmosphere for 24 hours to obtain modified cellulose; 2. Add sodium alginate to deionized water at a mass volume ratio of 1 g: 100 mL, stir evenly at room temperature, add 10 mL of 3.5 wt% calcium chloride solution to the system, stir at 60 rpm for 10 minutes, freeze-dry the system at -40 ° C for 2 hours, then crush and pass through a 100 mesh sieve to obtain aerogel powder; mix the aerogel powder with the modified cellulose obtained in step S21 to obtain breathable particles; wherein the mass ratio of aerogel powder to modified cellulose is 1:0.2.

[0050] S2. Use the mother liquor obtained in step S1 to prepare a membrane. Ultrasonic mix the mother liquor for 10 minutes, then coat it on a stainless steel substrate, naturally cure it for 10 minutes, then wash it with deionized water for 3 times, and vacuum dry it under 1Pa and -55°C to obtain a polyurethane nano-scale microporous membrane for protective clothing.

[0051] Performance Testing The nano-scale microporous membranes prepared in Examples 1-3 and Comparative Examples 1-5 of the present application were made into samples with a specification of 20*20*0.2 cm. The microporous membrane samples prepared in different groups are now subjected to performance tests. Before the test, the sample test state is adjusted. The pre-humidification, humidity adjustment and test atmosphere should be carried out within the standard atmosphere and tolerance range specified in GB / T 6529. The state adjustment time is not less than 4 hours, and the test is carried out under this condition.

[0052] Breaking strength and elongation at break: Conduct the test in accordance with the provisions of GB / T 3923.1, calculate the average breaking strength of the effective specimens, and the result shall be accurate to 0.1N; calculate the average transverse and longitudinal breaking elongations of the effective specimens, and the results shall be accurate to 0.5%.

[0053] Waterproof performance: Tested in accordance with the provisions of GB / T 4744. The nano-microporous membrane needs to use a 60-mesh nylon mesh to support the sample. The nylon mesh size is a 20cm×20cm square mesh with a mesh size of about 0.3mm. It can simulate the role of the adhesive layer to prevent the sample from being torn or stretched by water.

[0054] Air permeability: Tested in accordance with GB / T 5453. The pressure drop of the test conditions is 200Pa and the results are retained to 0.01mm / s.

[0055] Water vapor permeability: Refer to GB / T 12704.1-2009, 3.1. The water vapor mass passing through the sample per unit area vertically within a specified time under the specified temperature and humidity conditions on both sides of the sample.

[0056] The specific performance test results are shown in Table 1 below.

[0057]

[0058] From the results shown in Table 1 above, it can be seen that the comprehensive performance of the nanoscale microporous membranes prepared in Examples 1-3 of the present application is significantly better than that of the products prepared in Comparative Examples 1-5, that is, within the technical solution defined in the present application, the comprehensive performance of the prepared nanoscale microporous membranes is excellent.

[0059] It can be seen from the results in Comparative Examples 1, 4 and 5 that acylation of silk fibroin and use it to reinforce nano-scale microporous membrane materials can improve the mechanical properties and air permeability of the membrane materials, and that after the silk fibroin is modified with a high degree of acylation, the hydrophilicity of the protein is reduced and the hydrophobicity of the membrane material is improved.

[0060] From the results of Comparative Examples 2 and 3, it can be seen that the carboxymethyl cellulose material also shows an enhancement effect on the mechanical properties of the prepared membrane material. After being modified by dopamine hydrochloride, the dispersion uniformity of the pore-forming agent is improved, the uniformity of the pores on the membrane material is improved, and thus the air permeability effect is improved.

[0061] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0062] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A process for preparing a polyurethane nano-scale microporous membrane for protective clothing, characterized in that: The method comprises the following preparation steps: S1, extracting silk fibroin, and hydrophobically modifying the silk fibroin to prepare modified silk fibroin; S2, mixing the modified silk fibroin obtained in step S1 with polyurethane in a solvent, stirring at room temperature until dissolved, adding a pore-forming agent and breathable particles to obtain a mother solution; S3, using the mother solution obtained in step S2 to prepare a membrane, thereby obtaining a polyurethane nano-scale microporous membrane for protective clothing; The breathable particles are obtained by mixing modified cellulose and aerogel powder.

2. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 1, characterized in that: In step S1, the modified silk fibroin is prepared by the following steps: S11, mixing urea and guanidine hydrochloride, and heating to obtain a protein sol solution; then chopping the silk fibers, adding them to the protein sol solution, stirring evenly, raising the system temperature for 20-30 hours, washing, filtering, and obtaining silk fibroin; S12. Add silk fibroin to deionized water, increase the system temperature to 50-60°C, stir, then add acetic anhydride and adjust the pH value of the system to 9-10, continue the reaction for 1-3 hours, then adjust the pH value of the system to neutral, dialyze at 0-4°C to obtain modified silk fibroin.

3. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 2, characterized in that: In step S12, the amount of silk fibroin and acetic anhydride used is 1:(0.2-0.3).

4. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 1, characterized in that: In step S2, the mass ratio of modified silk fibroin, polyurethane, pore-forming agent and breathable particles is (20-30):100:(5-10):(10-20).

5. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 1, characterized in that: The pore-forming agent is nano zinc oxide.

6. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 1, characterized in that: In step S3, the air permeable particles are specifically prepared by the following steps: S21, adding 2-morpholineethanesulfonic acid to deionized water, adjusting the pH value of the system to 5.5-6.7, and stirring the system at room temperature until dissolved to obtain 2-morpholineethanesulfonic acid buffer; dissolving carboxymethyl cellulose, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and dopamine hydrochloride in the 2-morpholineethanesulfonic acid buffer, and stirring at room temperature under an inert gas atmosphere to obtain modified cellulose; S22. Add sodium alginate into deionized water, stir evenly at room temperature, add calcium chloride solution into the system, stir for 10-30 minutes, freeze-dry, then crush and sieve to obtain aerogel powder; mix the aerogel powder with the modified cellulose obtained in step S21 to obtain breathable particles.

7. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 6, characterized in that: In step S21, the mass ratio of carboxymethyl cellulose to dopamine hydrochloride is (5-10):(0.1-1).

8. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 6, characterized in that: The mass ratio of aerogel powder to modified cellulose is 1:(0.2-0.4).

9. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 1, characterized in that: The specific operation of using the mother solution obtained in step S2 to prepare the membrane is as follows: The mother solution is ultrasonically mixed for 10-20 minutes, then coated on a substrate, naturally cured for 10-30 minutes, then washed with deionized water, and vacuum dried.

10. The process for preparing a polyurethane nano-scale microporous membrane for protective clothing according to claim 1, characterized in that: The polyurethane is a polyurethane material containing a benzene ring structure.

Citation Information

Patent Citations

  • Polyurethane waterproof moisture-permeable film and preparation method thereof

    CN111019332A

  • Hair color changing wig technology and manufacturing process thereof

    CN117127420A

  • Outer wall insulation board prepared from fly ash of garbage power plant and preparation method of outer wall insulation board

    CN117447231A

  • Photocatalyst nano material and preparation method thereof

    CN118204122A

  • Antibacterial hemostatic dressing based on alginate

    CN118453947A

Cited By

  • Oxidation-resistant high-strength stainless steel for oven and preparation method thereof

    CN120624925A